Evidence for possible genetic recombination in isolates of Magnaporthe grisea from Himachal Pradesh by DNA fingerprinting and plant inoculation assays - and S.S. GNANAMANlCKAM, N.N. NARAYANAN, D.V. DAYAKAR (Indian Phytopathology, 2002)
The population structure of Magnaporthe grisea in Himachal Pradesh state, India, was assessed using laboratory assays for mating type allele distribution, DNA fingerprinting and pathogenicity assays in 91 isolates collected from farmers' fields andthe Research Station at Palampur during 1997-98. The results showed that it is possible that recombination occurs in the field populations of M. grisea. However, the predominant distribution of the MATI-1 type in the Himachal Pradesh population suggeststhat sexual recombination, if it occurs, may not be very important for the epidemiology of this pathogen.